ОБ ЭФФЕКТИВНОСТИ СИСТЕМЫ КРЕДИТОВАНИЯ ПРЕДПРИНИМАТЕЛЬСТВА (International Journal of Innovative Technologies in Economy, 2018)
The credit activity of banks plays an important role in deciding the issue of financial support for entrepreneurship. It is important to correctly assess the range of risks associated with the financing of projects, the activities of enterprises, the quality and quantity of ensuring the return of the resources involved.Kazakh banks, providing small and medium-sized businesses with a range of services related to the financing of projects and economic activities, prefer the following forms of security: pledge of inventory, real estate, funds in accounts, securities, guarantees. In the EU, the most common pledge of real estate, funds in the accounts of the entrepreneur as a private person.The science of credit, as well as any other economic processes, can not claim completeness without knowledge of the laws that operate in this field. Economic laws, including credit laws, have two fundamental characteristics: necessity and materiality, which is the basis of the law. Knowledge of the law can come only if the need is already found.